Abnormal pupillary light reflex with chromatic pupillometry in Gaucher disease. (4th February 2014) - Narita, Aya; Shirai, Kentarou; Kubota, Norika; Takayama, Rumiko; Takahashi, Yukitoshi; Onuki, Takanori; Numakura, Chikahiko; Kato, Mitsuhiro; Hamada, Yusuke; Sakai, Norio; Ohno, Atsuko; Asami, Maya; et al.
Abstract The hallmark of neuronopathic Gaucher disease (GD) is oculomotor abnormalities, but ophthalmological assessment is difficult in uncooperative patients. Chromatic pupillometry is a quantitative method to assess the pupillary light reflex (PLR) with minimal patient cooperation. Thus, we investigated whether chromatic pupillometry could be useful for neurological evaluations in GD. In our neuronopathic GD patients, red light‐induced PLR was markedly impaired, whereas blue light‐induced PLR was relatively spared. In addition, patients with non‐neuronopathic GD showed no abnormalities. These novel findings show that chromatic pupillometry is a convenient method to detect neurological signs and monitor the course of disease in neuronopathic GD.